TWO HUNDRED FACES OF A VAMPIRE: LORD RUTHVEN’S INFLUENCE ON VAMPIRE CULTURE - Pérez, Francisco Javier Sánchez-Verdejo; Silva, Alexander Meireles da (Abusões, 2019)
Being born in the same monstruous night that witnessed the rise of Frankenstein monster, the vampire Lord Ruthven celebrates in 2019 two hundred years influencing vampire culture. As it happens in literature, John William Polidori’s creature spread his curse through the centuries creating attractive, aristocrat, sexually ambiguous and immoral male and female vampires. From Victorian penny dreadfuls, novellas and novels such as Varney, the Vampire, Carmilla and Dracula, to present novel as Interview with the Vampire, the short story “The Vampyre” established the character who walk among human beings as a predator who chooses his prey. Ruthven was directly shaped on Lord Byron personality and, similar to the famous English poet, was an elegant figure of high culture and refined manners who hid a wild, libertine, profoundly narcissist nature and irascible behaviour, traits that paradoxically became Byron and his literary counterpart, delightfully fascinating beings. Reflecting the Romantic esthetic of its time, Polidori’s short story instituted the vampire as a rebel beyond bourgeois social norms. Lord Ruthven was an undead and, threfore, was not bound to the concepts that rule the living ones. In this way, the vampire appeal to humanity hidden desires related to the anguish of death, to the perspective of the transcendence and to the fear of the consequences of this act abandoning human nature. These elements help understanding the cultural impact John William Polidori’s creation keep on exercising two hundred years after 1819 through “The Vampyre”.